2016
DOI: 10.1021/acsbiomaterials.5b00477
|View full text |Cite
|
Sign up to set email alerts
|

Combination Nanovaccine Demonstrates Synergistic Enhancement in Efficacy against Influenza

Abstract: H5N1 influenza virus has the potential to become a significant global health threat, and next generation vaccine technologies are needed. In this work, the combined efficacy of two nanoadjuvant platforms (polyanhydride nanoparticles and pentablock copolymer-based hydrogels) to induce protective immunity against H5N1 influenza virus was examined. Mice received two subcutaneous vaccinations (day 0 and 21) containing 10 μg of H5 hemagglutinin trimer alone or in combination with the nanovaccine platforms. Nanovacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…PVA (Fig. [17][18][19] This work builds upon our previous studies by systematically studying the safety and biocompatibility of the PVA-modified PBC gels and demonstrates that these novel materials can be developed as adjuvants for next generation vaccines. 15 Like our PBC system, PVA has gelation capabilities, often achieved through γ-irradiation-induced cross-linking or successive freeze/thaw cycles.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…PVA (Fig. [17][18][19] This work builds upon our previous studies by systematically studying the safety and biocompatibility of the PVA-modified PBC gels and demonstrates that these novel materials can be developed as adjuvants for next generation vaccines. 15 Like our PBC system, PVA has gelation capabilities, often achieved through γ-irradiation-induced cross-linking or successive freeze/thaw cycles.…”
Section: Introductionmentioning
confidence: 63%
“…39,40 Although the mechanism for elevated levels of circulating triglycerides and cholesterol is not clear, it has been suggested that this may be due in part either to the alteration of lipoprotein lipase, an enzyme responsible for hydrolysis of plasma triglycerides and lipid metabolism or the stimulation of 2-hydroxy-3-methylglutaryl-coenzyme-A reductase, an enzyme responsible for production of cholesterol in the mevalonate pathway. 18 The mechanism of action of oil emulsion adjuvants such as IFA is their ability to induce inflammation at the site of injection and activate macrophages and dendritic cells and production of pro-inflammatory cytokines. The PVAinclusive hydrogel formulations were also previously found to induce robust immune responses 17 and served as effective adjuvants, eliciting high antibody titers and effective protection in an influenza challenge study.…”
Section: Discussionmentioning
confidence: 99%
“…In order to design an IAV vaccine that provides optimal protection by inducing long-lived local (i.e., lungs) and systemic immune responses, we made use of our CPTEG:CPH polyanhydride nanovaccine platform. Our previous studies have shown that a 20:80 CPTEG:CPH copolymer-based nanoparticle formulation is an effective delivery vehicle for IAV antigens and generation of systemic immune responses when given s.c. (26). Therefore, in order to generate both lung-focused as well as systemic immunity, we designed an i.n.…”
Section: Iav-nanovax Induces Lung-resident Gc B Cells and Iav-specifimentioning
confidence: 99%
“…We have previously reported a novel polyanhydride [copolymers of 1,8-bis(p-carboxyphenoxy)-3,6-dioxoctane (CPTEG) and 1,6-bis(p-carboxyphenoxy)hexane (CPH)] nanoparticle-based vaccine platform that has shown great promise in inducing immunity when administered subcutaneously (s.c.) (24)(25)(26). This platform offers several distinct advantages: the particles degrade into biocompatible products, activate APC, maintain the stability of encapsulated antigen, enable dose sparing of the antigen, and may be stored at room temperature or higher for up to 4 months thus breaking the cold chain (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it will be advantageous to design delivery agents that also contain innate pathogen‐mimicking signatures. Although multiple nanoparticle delivery systems have been evaluated as vaccine delivery systems, polyanhydride nanoparticles have shown potential as excellent candidates because of their chemical properties, which promote superior antigen stability, provide sustained antigen release kinetics, and induce immune modulatory effects …”
Section: Introductionmentioning
confidence: 99%